Detection of pspA Gene (Pneumococcal Surface Protein A) in Streptococcus pneumoniae Isolated from COVID-19 Patients - Afrah Adnan Hashim; Alyaa Maan Abdelhameed (Academic Science Journal)
Coronavirus disease 2019 (COVID-19) is a severe worldwide health issue. For a long time, it has been known that viral respiratory infections predispose people to bacterial infections. This study is conducted on patients infected with COVID19 who are hospitalized at Baqubah teaching hospital, for the period from October - 2021 to January -2022 December, for age groups (15-80 years) and of both sexes. As 100 sputum samples are collected, in order to investigate secondary bacterial infections associated with the emerging corona virus, all samples are growth-positive (100%). During the laboratory diagnosis 64 Streptococcus pneumoniae isolates are obtained from the positive samples. The gene that encodes to Pneumococcal surface protein A (PspA) of Streptococcus pneumoniae was investigated in 10 clinical isolates using conventional PCR technique. The results showed that all selected isolates (100%) have pspA gene.